Decomposability of matrix polynomials with commuting coefficients into a product of linear factors - Shavarovskyy, B. Z. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
The list of known sets of factorizable matrix polynomials is supplemented by new sets of polynomials of this sort. The known set of nonfactorizable matrix polynomials is extended. These results can be applied to the study of polynomial equations and systems of differential equations with constant coefficients.